A 60-year-old male with gradual loss of tooth surface - Ahmed, Sageer; Hossain, Mozammal; Parvin, Chowdhury Afrina (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
This article has no abstract. The first 100 words appear below: A 60-year-old male came with complaints of a gradual loss of tooth surface structure on the upper left anterior tooth with no complaints of pain and hypersensitivity. He was very much concerned about the appearance of the tooth and developing any pathology and therefore wanted to get his tooth treated. Medical history was not contributory, proper history about foods and diet habits, occupational, para-functional, and other abnormal habits were recorded but nothing significant was notified. The only significant was the horizontal brushing technique.